2012
DOI: 10.3138/ptc.2011-27
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Models of Service Delivery, Staffing, and Caseloads: A Profile of Level I Trauma Centres across Canada

Abstract: Purpose: To examine and describe physiotherapy models of service delivery, staffing, and caseloads in Level I trauma centres across Canada. Methods: A telephone questionnaire was administered to one experienced trauma physiotherapist at each of the 19 Level I trauma centres in Canada. Quantitative data were analyzed descriptively for national trends. Results: Data were collected from all 19 centres (100%), 89% of which provided physiotherapy services 5 days per week with priority weekend coverage. Physiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The variability in service provision described in this study is similar to that found in 2012 within Canadian MTS (Fisher et al 2012). These authors' research focused on models of service delivery in relation to specific hospital management structures and physiotherapy patient caseload numbers, particularly examining how the state of Ontario compared to the rest of Canada.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The variability in service provision described in this study is similar to that found in 2012 within Canadian MTS (Fisher et al 2012). These authors' research focused on models of service delivery in relation to specific hospital management structures and physiotherapy patient caseload numbers, particularly examining how the state of Ontario compared to the rest of Canada.…”
Section: Discussionmentioning
confidence: 79%
“…In Canada, comparative work found great variability of physiotherapy service structure within their MTS but key findings included a five day a week full physiotherapy service to trauma patients with priority-only coverage at weekends. Additionally, the majority worked within a separate physiotherapy department structure, where management decisions and quality assurance focused on the best interests of the physiotherapy department as a whole rather than necessarily being patient or unit specific (Fisher et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…12 Two national surveys (from Canada and Australia) have investigated models of physiotherapy service delivery to patients with traumatic injuries, staffing levels and caseloads. 12,13 Both had excellent response rates (>92%) but demonstrated large variations in service provision with 22-30% of trauma units having a dedicated trauma physiotherapist. Little is known about other geographical locations, including those with developing healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…This concept of place is informed by the relational understanding of space and place advocated by Cummins et al [2] and ‘the event of place’ referred to by Massey [3]. The relational view of place includes elements such as nodes of networks, separated by social relational distance with populations of individuals who are mobile both daily and over their life course [2].…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with the relational view of place which sees ‘territorial divisions, services and infrastructure imbued with social power relations and cultural meaning’ [2], p. 1827. The conventional view of place as spaces with fixed geographical boundaries and services described in terms of fixed locations [2] is different to the relational view of ‘nodes of networks’; ‘constellations of connections’ [3] and complex circuitry with a multiplicity of linkages and feedback loops [4]. Conceptual representation of conventional and relational space is provided Figure 1.…”
Section: Introductionmentioning
confidence: 99%